Pengaruh Kecerdasan Emosional, Kecerdasan Intelektual, Dan Perilaku Belajar Terhadap Tingkat Pemahaman Akuntansi Pada Mahasiswa Akuntansi Syariah Fakultas Ekonomi Dan Bisnis Islam UIN Sumatera Utara - Miatri Hasanah; Ahmadi Bi Rahman; Arnida Wahyuni Lubis (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
Abstract This research is based on the influence of emotional intelligence, intellectual intelligence and learning behavior on the level of understanding of accounting among sharia accounting students at UIN North Sumatra. Emotional intelligence is self-control, intellectual intelligence is reasoning, learning behavior is a person's attitude in the learning process, and accounting understanding is the ability to identify and measure financial information. This research aims to determine the influence of Emotional Intelligence, Intellectual Intelligence, and Learning Behavior on the level of Accounting Understanding among Sharia Accounting Students, Faculty of Economics and Islamic Business, UIN North Sumatra. This research uses a quantitative approach method with associative analysis, data collection techniques using questionnaires and the sample in this research was 83 Sharia Accounting Students FEBI UIN North Sumatra using the Purposive Sampling technique. Data were analyzed using multiple linear regression methods. The results of the research based on a partial test with a significant figure of 5% with a ttable of 1.990 show that the Emotional Intelligence variable has no effect on the level of Accounting Understanding as shown by tcount < ttable with tcount for variable X1(-1.059). And it shows that the Intellectual Intelligence variable has no effect on the level of Accounting Understanding tcount < ttable with tcount for Variable X2 (-0.260). Meanwhile, the Learning Behavior variable influences the level of Accounting Understanding as shown in tcount > ttable with tcount for variable X3 (2.388). The research results from the simultaneous test hypothesis with a significant figure of 5% with Fcount of 2.322 and Ftable of 2.72 shown by Fcount >Ftable shows that Emotional Intelligence, Intellectual Intelligence, and Learning Behavior influence the level of Accounting Understanding of Sharia Accounting Students, Faculty of Economics and Islamic Business, UIN North Sumatra.